Eyes in the sky, Polisens användning av drönare och dess undantag från upplysningsplikten. - Jademyr,Jonathan (2021)
Swedish camera surveillance legislation has since 1977 contained requirements for permits, a consideration of the involved interests, and a duty to inform the surveilled. This applies to both authorities and citizens alike. The exceptions to these obligations have been few and restrictive. Over the years, surveillance legislation has been modernized to keep up with technological developments and public opinion. This was most recently done through the kamerabevakningslagen (2018: 1200), where the legislators chose to remove the requirements of permits for the police use of camera surveillance in crime preventive purposes. Furthermore, the law opened up opportunities to make exceptions from the required consideration of the involved interests in cases of so-called urgent circumstances. Exceptions were also made from the duty to inform the surveilled when using aerial vehicles. These exemptions make it possible, albeit in specific cases, to use drone surveillance without permit requirements, a consideration of the involved interests, and the duty to inform the surveilled. The essay uses a legal development perspective and has studied the Swedish camera surveillance legislation's development through the history from the Lag om TV-övervakning to today’s Kamerabevakningslag. Furthermore, a legal dogmatic method has been used to investigate current law as well as historic laws. This has been done through a review of official reports and preparatory works. A review of the fundamental rights that an EU citizen can expect is then combined with a description of what personal integrity means for the individual. Finally, the essay describes the problems that have emerged regarding a lack of protection for personal integrity.
Keywords: Polismyndigheten; Kamerabevakningslag; Offentlig rätt; UAS; Statsrätt